INFLUENCE OF DRINKING WATER QUALITY ON LEVEL OF POPULATION HEALTH IN POLTAVA REGION IN 2001–2002 - Степаненков, Г. В. (Scientific Progress & Innovations, 2015)
The influence of drinking water quality on the level of population health in Poltava region is considered, and the results of the research are given. The obtained results are shown in the graphs and calculated correlation coefficients. Graphs are shown both for the total incidence in the area and for two the most common groups of diseases (blood circulatory system diseases, diseases of the musculoskeletal system and connective tissue). It has been proved that the quality of drinking water in the region has a significant effect on human health. Appropriate general conclusions are drawn.